Reformulasi Kuota Haji Indonesia: Prospektif Kebijakan, Advokasi dan Kontra Narasi Isu Politis - HM Affan Rangkuti (Biro Perencanaan Kementerian Agama, 2023)
Indonesian Hajj Quota Reform: Policy Prospectives, Advocacy & Counter Narrative Political Issues Abstract: The lengthy waiting time for Indonesian pilgrims is one of sensitive issues that public feels have never been resolved throughout any Hajj season. It is crucial and necessary to do research to support the government in formulating tactical and strategic efforts. This research may also be utilized as public advocacy to reconcile pilgrims and halt the flow of political decline in the performance of the Directorate General of Hajj and Umrah, Ministry of Religious Affairs of the Republic of Indonesia. The Ministry, as the operator of the Hajj organization, is responsible for resolving any concerns that may arise. The research uses a quantitative method with graphic visualization based on the latest data on congregations, hajj quotas, policies, and data-driven research results. Keyword: Hajj; Hajj Quota; Hajj Waiting Period.